国有企业改革与治理结构研究 = Research in reform & management structure of state-owned enterprises (SOEs) - 李国斌 Li, Guo Bin (2008)
The current SOE reform and management structure on China are examined based in the related economic theories. The comparison between classical SOE reform and standardizing corporation management structure are made. Lastly, the reform policies towards improving the SOE management structure are proposed.